ANALYSIS OF STUDENTS' ERRORS IN SOLVING ALGEBRAIC PROBLEMS BASED ON THE STAGES OF KRULIK AND RUDNICK IN GRADE IX JUNIOR HIGH SCHOOL - Budi Halomoan Siregar; Esther Veronica Putri Siregar; Lutfiah Syahrawani Siregar; Novitasari Br Hutauruk; Yulita Rotua Putri S. Sihite (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Problem-solving ability is one of the essential competencies in mathematics learning, particularly in algebra. However, in the problem-solving process, students often make errors that indicate difficulties in understanding concepts and determining appropriate solution strategies. This study aims to analyze students' errors in solving algebra problems based on the problem-solving stages proposed by Krulik and Rudnick, which include reading and thinking, exploring and planning, selecting a strategy, finding an answer, and reflecting and extending. This research employed a descriptive qualitative approach involving 24 ninth-grade junior high school students. The data were collected through a problem-solving test consisting of five algebra questions and analyzed based on the stages of problem solving. The results indicate that students' problem-solving abilities vary at each stage. A total of 83% of students were able to understand the problem at the read and think stage, 75% were able to plan the solution at the explore and plan stage, and 71% were able to select an appropriate strategy at the select a strategy stage. At the find an answer stage, the success rate decreased to 67% due to procedural errors in algebraic calculations. The lowest level of success occurred at the reflect and extend stage, where only 50% of students rechecked their answers. The dominant errors found include procedural errors in calculations, conceptual errors in understanding algebraic concepts, and difficulties in translating word problems into mathematical models.